If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y-(4y+6)=26
We simplify the equation to the form, which is simple to understand
6y-(4y+6)=26
Remove unnecessary parentheses
6y-4y-6=26
We move all terms containing y to the left and all other terms to the right.
+6y-4y=+26+6
We simplify left and right side of the equation.
+2y=+32
We divide both sides of the equation by 2 to get y.
y=16
| 4-6x=5x | | 1/20*5/10 | | -4(x-3)+6x=-32 | | 1/20-5/10 | | 2x+7-6x=2(x+10) | | -6=y/-4 | | j-2.4=1.9 | | -6(3x-5)+1=-18x+31 | | 14-2w+10w=34 | | 7/10*38/14*11/19 | | (9a+5)(3a^2+3a+4)= | | 4(3r+2)-3r=-10 | | -4=q/5 | | 3/10+3/14 | | 5b^6/7b | | t-9.6=1.7 | | 0.18(y-1)+0.10y=0.04y-1.2 | | 6+11z-2=9z+68-6z | | 25/28*4/51*17/50 | | 2(3x+6)=136 | | y/12+4=-7 | | -12-2+14=17 | | 9(x-2)+5=-13 | | (x+6)(x^3-3x+5)= | | 2x=16/9 | | x^2+y^2-6/5x+9/25-9=0 | | 6a+12=2a+-16 | | -4(7)+2(-9)-7(-9)=z | | 3*4/5 | | (x-4)(x^2-7x+2)= | | m+3m+4m+4= | | 2/6*3/4 |